Dietary epicatechin improves survival and delays skeletal muscle degeneration in aged mice. Issue 1 (10th August 2018) - Si, Hongwei; Wang, Xiaoyong; Zhang, Longyun; Parnell, Laurence D.; Ahmed, Bulbul; LeRoith, Tanya; Ansah, Twum-Ampofo; Zhang, Lijuan; Li, Jianwei; Ordovás, José M.; Si, Hongzong; Liu, Dongmin; et al.
ABSTRACT: We recently reported that epicatechin, a bioactive compound that occurs naturally in various common foods, promoted general health and survival of obese diabetic mice. It remains to be determined whether epicatechin extends health span and delays the process of aging. In the present study, epicatechin or its analogue epigallocatechin gallate (EGCG) (0.25% w/v in drinking water) was administered to 20‐mo‐old male C57BL mice fed a standard chow. The goal was to determine the antiaging effect. The results showed that supplementation with epicatechin for 37 wk strikingly increased the survival rate from 39 to 69%, whereas EGCG had no significant effect. Consistently, epicatechin improved physical activity, delayed degeneration of skeletal muscle (quadriceps), and shifted the profiles of the serum metabolites and skeletal muscle general mRNA expressions in aging mice toward the profiles observed in young mice. In particular, we found that dietary epicatechin significantly reversed age‐altered mRNA and protein expressions of extracellular matrix and peroxisome proliferator–activated receptor pathways in skeletal muscle, and reversed the age‐induced declines of the nicotinate and nicotinamide pathway both in serum and skeletal muscle. The present study provides evidence that epicatechin supplementation can exert an antiaging effect, including an increase in survival, an attenuation of the aging‐related deterioration of skeletal muscles, and a protection against the aging‐related decline in nicotinate and nicotinamide metabolism.—Si, H., Wang, X., Zhang, L., Parnell, L. D., Ahmed, B., LeRoith, T., Ansah, T.‐A., Zhang, L., Li, J., Ordovás, J. M., Si, H., Liu, D., Lai, C.‐Q. Dietary epicatechin improves survival and delays skeletal muscle degeneration in aged mice. FASEB J. 33, 965–977 (2019). www.fasebj.org